2020
DOI: 10.1007/s11764-020-00906-7
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative financial stress as a potential risk factor for cancer-related fatigue among prostate cancer survivors

Abstract: Introduction Cancer-related fatigue (CRF) is the most commonly reported treatment-related side effect of prostate cancer (PCa). Recognition of financial hardship among cancer survivors is growing. We investigated, for the first time, associations between levels of financial stress and CRF among PCa survivors. Methods We used data from PCa survivors who had been identified through two population-based cancer registries covering the Republic of Ireland and Northern Ireland and had completed a postal questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 69 publications
(87 reference statements)
0
19
0
Order By: Relevance
“…Which (long-term) physical issues develop mainly depends on the location of the primary tumor and the type of treatment received [ 42 , 43 , 44 ]. Compared to siblings and the general population with no history of cancer, AYAs are at greater risk of potentially life-threatening chronic medical conditions [ 43 , 44 , 45 ]. These long-term complications can lead to significant medical expenses and healthcare utilization [ 45 ].…”
Section: What Do We Know About Long-term and Late Effects Among Aya Cancer Survivors?mentioning
confidence: 99%
See 1 more Smart Citation
“…Which (long-term) physical issues develop mainly depends on the location of the primary tumor and the type of treatment received [ 42 , 43 , 44 ]. Compared to siblings and the general population with no history of cancer, AYAs are at greater risk of potentially life-threatening chronic medical conditions [ 43 , 44 , 45 ]. These long-term complications can lead to significant medical expenses and healthcare utilization [ 45 ].…”
Section: What Do We Know About Long-term and Late Effects Among Aya Cancer Survivors?mentioning
confidence: 99%
“…Compared to siblings and the general population with no history of cancer, AYAs are at greater risk of potentially life-threatening chronic medical conditions [ 43 , 44 , 45 ]. These long-term complications can lead to significant medical expenses and healthcare utilization [ 45 ].…”
Section: What Do We Know About Long-term and Late Effects Among Aya Cancer Survivors?mentioning
confidence: 99%
“…As with all studies, DUET has limitations which include a significant overrepresentation of breast cancer survivors (many of whom are upper-socioeconomic), and few dyads with rural residence. These are common limitations that have been reported by other research teams [ 47 , 48 , 49 ]. To address these concerns, future studies might consider preferentially accruing from support groups that focus on other types of cancer and community cancer centers in smaller towns (rather than major tertiary oncologic care centers).…”
Section: Discussionmentioning
confidence: 90%
“…The majority of the studies (21/29 or 72%) were published between 2011-2021 [20-25, 27-32, 35, 36, 38-40, 42-45] and from authors in academia (22/29 or 76%) [18-27, 29-34, 36-41]. Regarding geographic coverage, all but one study [25] (97%) included English data and 10 studies (35%) reported UK-wide data [18,20,28,29,36,[41][42][43][44][45]. 24 were peerreviewed articles [17][18][19][20][21][22][23][24][25][26][27][29][30][31][32][33][34][35][36][37][38][39][40][41] and 5 were grey literature (in the form of reports from charity organisations [42][43][44][45] and commentary from a freelance writer and welfare rights adviser [28]).…”
Section: Extent Nature and Distribution Of Studiesmentioning
confidence: 99%